2010
DOI: 10.1007/s10457-010-9291-1
|View full text |Cite
|
Sign up to set email alerts
|

Coffee agroforestry systems in Central America: II. Development of a simple process-based model and preliminary results

Abstract: Research on coffee agroforestry systems in Central America has identified various environmental factors, management strategies and plant characteristics that affect growth, yield and the impact of the systems on the environment. Much of this literature is not quantitative, and it remains difficult to optimise growing area selection, shade tree use and management. To assist in this optimisation we developed a simple dynamic model of coffee agroforestry systems. The model includes the physiology of vegetative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…To date, the framework of a conservative LUE (Monteith & Moss 1977;Paul & Foyer 2001) has been widely applied in crop and vegetation epsilon models to infer NPP (Cramer et al 1999;Paul & Foyer 2001), even in agroforestry (Monteith et al 1991;Charbonnier et al 2014). Although several models either adjust the maximum value of LUE as a function of stresses, apply a separate LUE for sunlit and shade leaves (Paul & Foyer 2001;Zhou et al 2015) or derive LUE from Farquhar biochemical model of photosynthesis (Paul & Foyer 2001;van Oijen et al 2004;van Oijen et al 2010), none incorporate such a large intra-plot variability of LUE, as shown in our study in an heterogeneous system. We argue here that models which are able to adjust LUE explicitly with fine resolution in heterogeneous systems have the potential to improve the reliability of GPP predictions dramatically, for plants and for plots.…”
Section: Importance Of Variable Light-use Efficiency For Modellingmentioning
confidence: 96%
“…To date, the framework of a conservative LUE (Monteith & Moss 1977;Paul & Foyer 2001) has been widely applied in crop and vegetation epsilon models to infer NPP (Cramer et al 1999;Paul & Foyer 2001), even in agroforestry (Monteith et al 1991;Charbonnier et al 2014). Although several models either adjust the maximum value of LUE as a function of stresses, apply a separate LUE for sunlit and shade leaves (Paul & Foyer 2001;Zhou et al 2015) or derive LUE from Farquhar biochemical model of photosynthesis (Paul & Foyer 2001;van Oijen et al 2004;van Oijen et al 2010), none incorporate such a large intra-plot variability of LUE, as shown in our study in an heterogeneous system. We argue here that models which are able to adjust LUE explicitly with fine resolution in heterogeneous systems have the potential to improve the reliability of GPP predictions dramatically, for plants and for plots.…”
Section: Importance Of Variable Light-use Efficiency For Modellingmentioning
confidence: 96%
“…Weather generator interpolation algorithms must be employed to derive estimates of daily time series (e.g. Van Oijen et al 2010).…”
Section: Weather Datamentioning
confidence: 99%
“…Providing empirical evidence on which factors explain the largest proportion of ITV in coffee (and other crops) is critical for refining trait sampling designs (e.g. Carmona et al 2015) and for integrating ITV into crop models (van Oijen et al 2010;Charbonnier et al 2013).…”
Section: Introductionmentioning
confidence: 99%